Juxtaposition Of Right To Self-determination And Terrorism Under International Law - Farzanah Selamat; Norfadhilah Mohamad Ali; Hendun Abd. Rahman Shah (Universiti sains Islam Malaysia, 2024)
Malaysian Journal of Syariah and Law Volume 11 No.2 Page (187-201)